2003
DOI: 10.1002/ptr.1251
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effect of aqueous extract of Nigella sativa seeds on nitric oxide production

Abstract: The in vitro effect of aqueous extract of Nigella sativa seeds on nitric oxide (NO) production by murine macrophages was studied. Murine peritoneal macrophages were pre-incubated with the extract and then activated with Escherichia coli lipopolysaccharride. NO production was measured after 24 hours by spectrophotometry. The plant extract caused a dose-dependent decrease in NO production. Dialyzed preparation of the extract did not affect NO production. However, the boiled fraction of the extract resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 24 publications
6
46
0
Order By: Relevance
“…Our results are consistent with the results of Wolff (1993), ElMissiry and El-Gindy (2000), and Mahmood et al (2003) who reported an increase in lipid peroxides and a decrease in antioxidant enzymes in diabetes mellitus. Schettelar et al (1994) suggested that the reduced antioxidant production was due to increased oxygen metabolites causing a decrease in the activity of the antioxidant defense system.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the results of Wolff (1993), ElMissiry and El-Gindy (2000), and Mahmood et al (2003) who reported an increase in lipid peroxides and a decrease in antioxidant enzymes in diabetes mellitus. Schettelar et al (1994) suggested that the reduced antioxidant production was due to increased oxygen metabolites causing a decrease in the activity of the antioxidant defense system.…”
Section: Discussionsupporting
confidence: 93%
“…The antimalarial activity may be due to the antioxidant effect of its alkaloids. It has been postulated that its antioxidant components might inhibit nitric oxide (NO) production in macrophages which will lead to increased degradation of tryptophan and thereby starve the parasite of an essential amino acid leading to its death 49,50 . Different extracts of enanthiachloranthia have also been reported to exert antimicrobial activities including antibacterial 51,52 However, the use of these herbs in the very young are of major concern.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood et al [41] stated that the aqueous extract of NS seeds exhibited an inhibitory effect on nitric oxide production by murine macrophages. Many studies have revealed that the modulation of the balance between nitric oxide (NO) production and lipid peroxidation products might play a major role in the increase of drug-induced cytotoxic effect [42,43] .…”
Section: Discussionmentioning
confidence: 99%